Effect of pH on complex formation between debranched waxy rice starch and fatty acids - Yotsawimonwat S. (2014)
Complex formations between debranched waxy rice starch (DBS) and fatty acids (FA) of different hydrocarbon chain lengths (8:0, 10:0, 12:0, 14:0, 16:0, and 18:0) were studied in an aqueous solution by measuring the blue colour stained with iodine. The objective of this study was to understand the effects of the solubility and hydrophobicity of guest molecules (FA) on the complex formation with DBS. Lauric acid (12:0) displayed the greatest complex forming ability with DBS by showing the least blue colour developed with iodine. The effect of pH (3-7) on the DBS/FA complex formation was evaluated by measuring the iodine-scanning spectra of the mixture. Short-chain FA (8:0) displayed less complex formation at pH ≥ 5, above the pKa of fatty acid (∼4.8), which suggested that the charge formation of the short-chain FA caused a lower partitioning of the FA into the hydrophobic cavity of the DBS single helix. On the contrary, FA of 10:0-18:0 displayed an increased complex formation at pH > 5, which could be attributed to increased solubility of these longer-chain FA at a dissociated and ionized form. The hydrocarbon chain length of the FA had an important impact on the extent of the complex formation. A FA that had a shorter hydrocarbon chain was more soluble in an aqueous solution and more readily formed a complex with DBS. At pH 6 and 7 (above the pKa), 10:0 formed less inclusion complexes with DBS than did 12:0. Iodine-scanning spectra showed that the absorbances of all iodine-stained DBS/FA solutions at higher wavelength were substantially lower than that of the iodine-stained DBS alone, suggesting that FA preferentially formed inclusion complexes with DBS of longer chains. © 2008 Elsevier B.V.